Persepsi Pembaca Terhadap Puisi “Hujan Bulan Juni” Karya Sapardi Djoko Domono: Analisis Horizon Harapan dalam Perspektif Hans Robert Jauss - Yani, Indri; Nisa, Khairun; Arfiani, Nanda Tiara; Ulfa, Syafrina; Sinulingga, Gisella Dameri; Anggreini, Heny (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses the reader's reception of the poem "Hujan Bulan June" by Sapardi Djoko Damono using the horizon theory of hope in the perspective of Hans Robert Jauss. The poem depicts the themes of love, patience, and sacrifice in silence, with the metaphor of rain falling in June as a symbol of love that is not expressed directly. This research aims to analyze how readers understand and interpret the meaning of these poems based on their expectations, experiences, and cultural contexts. The approach used is a qualitative descriptive method with literature study techniques. The results of the study show that readers can interpret this poem through three dimensions: fortitude, wisdom, and sincerity in facing certain feelings or situations. The meaning of this poem is not fixed, but rather develops according to the reader's horizon of expectations, which is influenced by their social, cultural, and experience backgrounds